Right Hemisphere Prefrontal Cortical Involvement in Text-Speak Processing. (September 2013) - Head, James; Wilson, Kyle M.; Helton, William S.; Neumann, Ewald; Russell, Paul N.; Shears, Connie
As text-based communication increases in the civilian and military workplace (Finomore, Popik, Castle, & Dallman, 2010), so does the potential to encounter text-speak. It has been proposed that processing text-speak (I wll tlk 2 u l8tr, I will talk to you later) comes at a cognitive cost (Head, Helton, Russell, & Neumann, 2012). To the authors' knowledge, there have been no studies investigating the potential physiological cost of processing text-speak. In the current study we investigate the cognitive cost of processing text-speak by measuring performance on a dual-task while also measuring cerebral oxygenation in the prefrontal cortex. Sixty-four university students completed a dualtask which included a conscious priming task and a vigilance task. They also completed a text-speak questionnaire (Head, Helton, Russell, Neumann, & Shears, 2011). The behavioral results failed to show any significant difference in performance between text-speak and correctly spelled text. However, the physiological measurements revealed that the right prefrontal cortex has significantly greater activation when text-speak is shown, thus suggesting a RH compensatory effect. A significant correlation between the text-speak questionnaire and right-hemisphere activation suggests that the right-hemisphere contains the cognitive tools for overriding potential difficulties in processing textspeak.